A novel neutralizing monoclonal antibody recognizes a linear antigenic epitope of the spike protein of swine acute diarrhoea syndrome coronavirus - Lin Zhang; Hui-Zhen Liu; Yuexiao Lian; Yujun Zhu; Miaoli Wu; Jianbo Liu; Feng Cong (Virology Journal)
Abstract Swine acute diarrhoea syndrome coronavirus (SADS-CoV) causes vomiting, severe diarrhoea and death in newborn piglets. The spike (S) protein plays a crucial role in promoting virus invasion and inducing neutralizing antibody production. In this study, the extracellular region of the S protein was used as an immunogen to immunize BALB/c mice. After immunization, B cells were collected, fused with SP2/0 myeloma cells, cultured and subcloned, and a cell line capable of secreting neutralizing antibodies was obtained and named as 5D6. Additionally, it was determined that the 5D6 mAb could be used as the primary antibody for western blotting and indirect immunofluorescence assay (IFA) to detect SADS-CoV. Further studies indicated that the 5D6 mAb binds to the 136STSHAAD142 motif, which located in the N-terminal domain (NTD) of the spike protein. This result suggested that the NTD of the S protein can induce the production of neutralizing antibodies. Amino acid sequence alignment revealed that the epitope of the 5D6 mAb was conserved among SADS-CoV strains. This study helps elucidate the S protein function of SADS-CoV, and the 5D6 mAb may be used to develop diagnostic and treatment tools for detecting SADS-CoV infection.